Multispacecraft current estimates at swarm. Issue 10 (3rd October 2015) - Dunlop, M. W.; Yang, Y.‐Y.; Yang, J.‐Y.; Lühr, H.; Shen, C.; Olsen, N.; Ritter, P.; Zhang, Q.‐H.; Cao, J.‐B.; Fu, H.‐S.; Haagmans, R.
Abstract: During the first several months of the three‐spacecraft Swarm mission all three spacecraft came repeatedly into close alignment, providing an ideal opportunity for validating the proposed dual‐spacecraft method for estimating current density from the Swarm magnetic field data. Two of the Swarm spacecraft regularly fly side‐by‐side in closely similar orbits, while the third at times approaches the other two. This provides a data set which under certain assumptions of stationarity of the magnetic field can produce 2, 3, 4, 5 (or more) point measurements, which can be cross compared. We find that at low Earth orbit the use of time‐shifted positions allow stable estimates of current density to be made and can verify temporal effects as well as validating the interpretation of the current components as arising predominantly from field‐aligned currents. In the case of four‐spacecraft configurations we can resolve the full vector current and therefore can check the perpendicular as well as parallel current density components directly, together with the quality factor for the estimates directly (for the first time in situ at low Earth orbit). Key Points: Two‐, three‐, and four‐point analyses of electric currents at low Earth orbit Comparative analysis of field‐aligned current density: test of stability Direct measure of perpendicular currents in the upper ionosphere for the first time